2016
DOI: 10.1088/1538-3873/128/970/124204
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismic Properties of Solar-type Stars Observed with the NASAK2Mission: Results from Campaigns 1–3 and Prospects for Future Observations

Abstract: We present an asteroseismic analysis of 33 solar-type stars observed in short cadence during Campaigns (C) 1-3 of the NASA K2 mission. We were able to extract both average seismic parameters and individual mode frequencies for stars with dominant frequencies up to ∼3300 µHz, and we find that data for some targets are good enough to allow for a measurement of the rotational splitting. Modelling of the extracted parameters is performed by using grid-based methods using average parameters and individual frequenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 119 publications
0
19
0
Order By: Relevance
“…[Fe/H] comes from spectroscopic observations from the APOGEE survey (Majewski et al 2017). Lund et al (2016) present an asteroseismic analysis of 33 solar-like stars observed by the K2 mission. The modeling of M, R, and ρ was done through grid-based modeling using the Bayesian Stellar Algorithm (BASTA; Silva Aguirre et al 2015) and GARSTEC.…”
Section: Data Samplementioning
confidence: 99%
“…[Fe/H] comes from spectroscopic observations from the APOGEE survey (Majewski et al 2017). Lund et al (2016) present an asteroseismic analysis of 33 solar-like stars observed by the K2 mission. The modeling of M, R, and ρ was done through grid-based modeling using the Bayesian Stellar Algorithm (BASTA; Silva Aguirre et al 2015) and GARSTEC.…”
Section: Data Samplementioning
confidence: 99%
“…The noise model applied in the detection probability test follows that first proposed for Kepler in Chaplin et al (2011b), modified for the noise performance of K2 by Lund et al (2016). The procedure predicts the expected global signal-to-noise level in the detected oscillations against background from intrinsic stellar noise (granulation) and shot/instrumental noise.…”
Section: Selection Functionmentioning
confidence: 99%
“…[h] Table 2. Comparisons of our measurements with those from other works: the GALAH survey (Buder et al 2018a), the GALAH-TGAS survey (Buder et al 2018b), K2 asteroseismology parameters (Lund et al 2016) and the TESS Input Catalog (Stassun et al 2018). We for all but the asteroseismology comparison we divide our sample into evolved stars (where the comparison survey measures log g < 4) and dwarfs of different spectral classes.…”
Section: Acknowledgmentsmentioning
confidence: 98%
“…To further test our stellar parameter measurements we also compared our results with objects in the GALAH-TGAS survey (a separate stellar parameter calculation from the main GALAH survey using GALAH spectra and GAIA TGAS parallaxes Buder et al 2018b), K2 asteroseismology parameters (Lund et al 2016) and the aforementioned TESS Input Catalog (Stassun et al 2018). We note that the GALAH-TGAS survey includes some of the astrometric data that went into the Gaia parallaxes we use, hence it is not entirely independent.…”
Section: Comparison To Other Stellar Parameter Estimatesmentioning
confidence: 99%